A semi-automated approach for GIS based generation of topographic attributes for landform classification - Metternicht, Graciela; Klingseisen, B.; Paulus, G. (The International Cartographic Association (ICA-ACI), 2005)
This paper presents LANDFORM, a customized GIS application for semi-automated classification of landform elements, based on landscape parameters. Using custom commands, topographic attributes like curvature or elevation percentile were derived from a Digital Elevation Model (DEM) and used as thresholds for the classification of Crests, Flats, Depressions and Simple Slopes. With a new method, Simple Slopes were further subdivided in Upper, Mid and Lower Slopes at significant breakpoints along slope profiles. The paper discusses the results of a fuzzy set algorithm that was used to compare the similarity between the map generated by LANDFORM and the visual photo- interpretation conducted by a soil expert over the same area. The classification results can be used in applications related to precision agriculture, land degradation studies, and spatial modelling applications where landform is identified as an influential factor in the processes under study.